Draft Genome Sequence of the Marine Bacterium Pseudomonas aestusnigri VGXO14(T) - Gomila, Margarita (Genome Announc, 2017)
The type strain of Pseudomonas aestusnigri (VGXO14), isolated from a crude oil-polluted marine sand sample, is a member of the P. pertucinogena phylogenetic group. Here, we report the genome sequence (3.83 Mb) of P. aestusnigri to gain insights into the biology and taxonomy of marine Pseudomonas spp. adapted to polluted marine habitats.